DIGITALIZATION OF THE GLOBAL ECONOMY AND ITS IMPACT ON INTERNATIONAL ECONOMIC PROCESSES - Balaban, Eugene; Hetmanenko, Oleksiy; Khmelevskyi, Oleh (Social Development: Economic and Legal Issues, 2026)
Digitalization has emerged as a key driver of economic growth and a supporting factor for economic sustainability, significantly influencing international economic processes and relations. Leading countries in the development of the digital economy are implementing national digitalization strategies or creating a favorable fiscal and tax environment to attract investment in innovative projects that promote digitalization and the development of industrial zones with a high concentration of advanced technology manufacturers. The purpose of this article is to examine the impact of economic digitalization on international economic processes, including the development of industrial zones. The study applies methods of analyzing strategic documents of governments in the EU, East Asia, and Northern Europe to identify strategic directions for digitalization and the scale of their financing. To assess the level of economic digitalization, the dynamics of high-tech product exports by world regions over 2014–2024 and the trends in ICT goods exports and imports during 2000–2022 were analyzed. The results demonstrate the significant role of state policy and public financing in economic digitalization. In the EU, financing of innovative projects in high-tech sectors prevails. In the USA, the Chips and Science Act (2022) provides subsidies for producers of critical technologies in artificial intelligence, quantum computing, and green energy. In China, five-year digital economy plans are aimed at increasing the added value of high-tech industries. Using the United States as an example, it was found that a favorable fiscal and tax environment (including tax incentives, subsidies under state digitalization programs) contributes to the economic digitalization and directs private and foreign investment towards high-tech enterprises. The study shows a significant impact of digitalization strategies on foreign direct investment flows into high-tech sectors in countries that have created supportive fiscal and tax conditions for innovative development. A relationship is identified between public financing of digitalization, the development of high-tech sectors, and the transformation of international economic processes through the attracting of FDI and the formation of digital industrial clusters.